2010
DOI: 10.1038/ni.1864
|View full text |Cite
|
Sign up to set email alerts
|

The AIM2 inflammasome is essential for host defense against cytosolic bacteria and DNA viruses

Abstract: Inflammasomes regulate the activity of capase-1 and maturation of interleukin-1β and interleukin-18. Recently, AIM2 was shown to bind DNA and engage ASC to form a caspase-1 activating inflammasome. Using Aim2-deficient mice, we reveal a central role for AIM2 in regulating caspase-1-dependent maturation of IL-1β and IL-18, as well as pyroptosis in response to synthetic dsDNA. AIM2 is essential for inflammasome activation in response to Fransicella tularensis, vaccinia virus, mouse cytomegalovirus and plays a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
1,122
2
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,167 publications
(1,170 citation statements)
references
References 54 publications
39
1,122
2
7
Order By: Relevance
“…6 AIM2 is activated by viral, bacterial, and host ectopic dsDNA and induces cleavage of procaspase-1, maturation of IL-1b, and pyroptosis. 7 Although AIM2 is expressed in tissue outside the immune system, 8 its functional role in either the recognition of pathogenic DNA, or autoimmune reactions to host nucleic acids, has only been established in innate immune cells. It is unknown if AIM2 regulates the innate immune response to dsDNA in other cell types, such as neurons.…”
Section: Introductionmentioning
confidence: 99%
“…6 AIM2 is activated by viral, bacterial, and host ectopic dsDNA and induces cleavage of procaspase-1, maturation of IL-1b, and pyroptosis. 7 Although AIM2 is expressed in tissue outside the immune system, 8 its functional role in either the recognition of pathogenic DNA, or autoimmune reactions to host nucleic acids, has only been established in innate immune cells. It is unknown if AIM2 regulates the innate immune response to dsDNA in other cell types, such as neurons.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, studies have shown a direct interaction between murine cytomegalovirus (MCMV) and NK cells, where the activating NK cell receptor Ly49H recognizes the m157 glycoprotein, thereby activating the NK cell to produce cytokines important for antiviral immunity and/or to kill (Krug et al 2004;Varani et al 2007;Zucchini et al 2008) MCMV and HCM-V AIM2 dsDNA (Rathinam et al 2010;Huang et al 2017) MCMV and HCM-V cGAS-STI-NG dsDNA (Lio et al 2016) MCMV TLR3 dsRNA (Tabeta et al 2004) MCMV TLR7 ssRNA (Zucchini et al 2008) HCMV DAI dsDNA (DeFilippis et al 2010) HCMV IFI16 dsDNA (Gariano et al 2012) the virus-infected cell through release of perforins and granzymes (Brown et al 2001;Pyzik et al 2011). Indeed, m157 deletion mutant MCMV fails to activate Ly49H+ NK cells and results in enhanced virulence (Voigt et al 2003;Bubić et al 2004).…”
Section: Innate Immunitymentioning
confidence: 99%
“…Strikingly, it recognizes the mammalian DNA which acts as a contributory factor toward the pathogenesis of autoimmune diseases. 40 The association of helicase receptor RIG of dsRNA with the inflammasome adaptor molecule ASC leads to inflammasome activation which triggers caspase-1 activation. 41 Inflammasome Activates Caspase-1…”
Section: Aim2 Inflammasomementioning
confidence: 99%
“…65,66 In vivo studies have highlighted low levels of serum IL-18 and less secretion of interferon-g (IFN-g) by splenic NK cells in AIM2 deficient mice infected with mCMV. 66 Likewise, AIM2 deficient mice infected with F. tularensis novicida have high bacterial loads, low levels of serum IL-18 and lower survival than do wild type mice. 65 Mice deficient in ASC or caspase-1 show similar phenotype as described for the AIM2 deficient mice.…”
Section: Intracellular Pathogens and The Inflammasomesmentioning
confidence: 99%
See 1 more Smart Citation